BOSS Great Wall: morphology, luminosity, and mass - Einasto M; Lietzen H; Gramann M; Saar E; Tempel E; Liivamagi LJ; Montero-Dorta AD; Streblyanska A; Maraston C; Rubino-Martin JA (EDP SCIENCES S A, 2022)
Context. Galaxy superclusters are the largest systems in the Universe that can give us information about the formation and evolution of the cosmic web.Aims. We study the morphology of the superclusters from the BOSS Great Wall (BGW), a recently discovered very rich supercluster complex at the redshift z = 0.47.Methods. We have employed the Minkowski functionals to quantify supercluster morphology. We calculate supercluster luminosities and masses using two methods. Firstly, we used data about the luminosities and stellar masses of high stellar mass galaxies with log(M-*/h(-1) M-circle dot) >= 11.3. Secondly, we applied a scaling relation that combines morphological and physical parameters of superclusters to obtain supercluster luminosities, and obtained supercluster masses using the mass-to-light ratios found for local rich superclusters.Results. The BGW superclusters are very elongated systems, with shape parameter values of less than 0.2. This value is lower than that found for the most elongated local superclusters. The values of the fourth Minkowski functional V-3 for the richer BGW superclusters (V-3 = 7 and 10) show that they have a complicated and rich inner structure. We identify two Planck SZ clusters in the BGW superclusters, one in the richest BGW supercluster, and another in one of the poor BGW superclusters. The luminosities of the BGW superclusters are in the range of 1-8x10(13) h(2) L-circle dot, and masses in the range of 0.4-2.1x10(16) h(1) M-circle dot. Supercluster luminosities and masses obtained with two methods agree well.Conclusions. The BGW is a complex of massive, luminous and large superclusters with very elongated shape. The search and detailed study, including the morphology analysis of the richest superclusters and their complexes from observations and simulations can help us to understand formation and evolution of the cosmic web.